A Primary Male Autosomal Linkage Map of the Horse Genome - Lindgren, Gabriella (Cold Spring Harbor Laboratory Press, 1998)
A primary male autosomal linkage map of the domestic horse (Equus caballus) has been developed by segregation analysis of 140 genetic markers within eight half-sib families. The family material comprised four Standardbred trotters and four Icelandic horses, with a total of 263 offspring. The marker set included 121 microsatellite markers, eight protein polymorphisms, five RFLPs, three blood group polymorphisms, two PCR–RFLPs, and one single strand conformation polymorphism (SSCP). One hundred markers were arranged into 25 linkage groups, 22 of which could be assigned physically to 18 different chromosomes (ECA1, ECA2, ECA3, ECA4, ECA5, ECA6, ECA7, ECA9, ECA10, ECA11, ECA13, ECA15, ECA16, ECA18, ECA19, ECA21, ECA22, and ECA30). The average distance between linked markers was 12.6 cM and the longest linkage group measured 103 cM. The total map distance contained within linkage groups was 679 cM. If the distances covered outside the ends of linkage groups and by unlinked markers were included, it was estimated that the marker set covered at least 1500 cM, that is, at least 50% of the genome. A comparison of the relationship between genetic and physical distances in anchored linkage groups gave ratios of 0.5–0.8 cM per Mb of DNA. This would suggest that the total male recombinational distance in the horse is 2000 cM; this value is lower than that suggested by chiasma counts. The present map should provide an important framework for future genome mapping in the horse.